FORMING OF ECONOMIC CONCEPTS IN PRIMARY SCHOOL STUDENTS - Sirant, Nelia (Continuing Professional Education: Theory and Practice, 2022)
students. The institution of primary education is the main key to economic education and the forming of economic concepts. On these grounds, is formed the students’ willingness to independent economic activity. Therefore, the content of curricula is improved to understand and form a variety of economic concepts for primary school students. The focus of attention is upon the requirements of great scientific motives, practical skills etc. The economy in primary school should be «transported» on the basis of knowledge, skills and abilities that students received in preschools and families. Students’ knowledge is integrated into the content of other educational fields of knowledge (mathematics, reading, technology, «I explore the world»), in particular primary school students ‒ this is the stage of acquiring basic life knowledge, skills and understanding processes, awareness of their own life experience and environment. Students are involved in the basics of economic literacy, accordingly, they form new economic thinking, get acquainted with the life of people and animals, their needs and ways to meet them, economic laws, creates a basis for further study of economic disciplines in secondary education. Ample attention is also paid to forming such concepts as «economics», «thrift» and «pupil» which are looked, at first sight, distant from each other. But if we consider it as a branch of «smart housekeeping», the economy is looked inseparable from the child from the first life years of the team. It has been underlined that the child’s first acquaintance with the basics of economic knowledge occurs in preschool, when, getting acquainted with the world around him, he first learns that the wealth of the family depends on the father’s and mother’s work, the money used to purchase necessary things in the store. At the same time, the child gets acquainted with such concepts as «price», «more expensive», «economy», «cost», «remainder» and «thrift».